Existence as a Real Predicate in Thomas Aquinas - Vargas, Rosa Elvira (2019)
It is often attributed to Aquinas the thesis that existence, unlike essence, cannot be the object of conceptualization. Arguably, without a concept of existence, Aquinas  offers an interpretation of existential propositions which closely resemble the modern analytic analysis. Accordingly, when wesay ‘P exists’, we attribute no property or special attribute to P. The purpose of this article is to show that for Thomas Aquinas, existence, like essence, can be the object of conceptualization nd functions as a real predicate. To that end, I base myself on Aquinas’ theory of signification.